Alveolar echinococcosis: what triggers emergence in North America, Central Europe and Asia?. Issue 5 (October 2021) - Gottstein, Bruno; Deplazes, Peter
Abstract : Purpose of review: Infection with the larval (metacestode) stage of Echinococcus multilocularis causes alveolar echinococcosis (AE), a serious hepatic disorder. The parasite has increased its infection extensity in wildlife and domestic dogs, mainly due to urbanization and spatial extension of wildlife hosts in Europe, Asia as well as North America, resulting in emerging infection risk for humans. Recent findings: In hyperendemic areas such as Kyrgyzstan and China, ecological and socioeconomic changes have been associated with the unpredictable increase of AE cases. In North America, the appearance of the European-like genotype is of concern. In Europe, the annual increase of human case numbers reached a plateau even in hyperendemic situations. Therefore, we conclude that most of the exposed individuals are resistant to parasite invasion and/or to disease development. Thus, AE develops in a few healthy individuals, but preferentially in immunosuppressed patients. Summary: In the future, improved diagnostic strategies will allow more precise estimations of transmission routes including the role of food, water and direct dog contact, which should yield improved public health recommendations. Finally, understanding protective innate and acquired immune mechanisms as well as parasite-driven immune-evasion processes will be essential to develop curative therapies in nonoperable patients and, futuristically, appropriate vaccines.